Kinesis: A New Approach to Replica Placement in Distributed Storage Systems - MacCormick, J.; Murphy, N.; Ramasubramanian, Rama; Wieder, Udi; Yang, J.; Zhou, Lidong (Transactions on Storage, 2008)
Kinesis is a novel data placement model for distributed storage systems. It exemplifies three design principles: structure (division of servers into a few failure-isolated segments), freedom of choice (freedom to allocate the best servers to store and retrieve data based on current resource availability), and scattered distribution (independent, pseudo-random spread of replicas in the system). These design principles enable storage systems to achieve balanced utilization of storage and network resources in the presence of incremental system expansions, failures of single and shared components, and skewed distributions of data size and popularity. In turn, this ability leads to significantly reduced resource provisioning costs, good user-perceived response times, and fast, parallelized recovery from independent and correlated failures. This paper validates Kinesis through theoretical analysis, simulations, and experiments on a prototype implementation. Evaluations driven by real-world traces show that Kinesis can significantly out-perform the widely-used Chain strategy for placing replicas; Kinesis saves resource requirements by up to 25%, improves end-to-end delay by up to 40%, and recovers from failures orders of magnitude times faster than Chain in our evaluations.